2021
DOI: 10.2147/jmdh.s287109
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Pregnancy: Beliefs, Benefits, and Information-Seeking Practices of Pregnant Women in South Africa

Abstract: Background Notwithstanding the benefits of physical activity (PA) during pregnancy, anecdotal evidence suggests ignorance, unscientific beliefs, and lack of awareness about PA among pregnant South African women. Aim This study examined the beliefs, perceived benefits, and sources of information on PA during pregnancy. Methods A cross-sectional descriptive study was employed between June and September 2019 using an interviewer-administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…However, prenatal physical activity and exercise have not been widely studied within the context of South Africa. To address this lack, a prenatal physical activity intervention strategy has been developed specifically for South Africa and is on the first empirical findings [24][25][26][27]. This timely move provides a unique contribution to, and lays the groundwork for, future prenatal physical activity intervention strategies, not only in the Eastern Cape Province but throughout South Africa as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prenatal physical activity and exercise have not been widely studied within the context of South Africa. To address this lack, a prenatal physical activity intervention strategy has been developed specifically for South Africa and is on the first empirical findings [24][25][26][27]. This timely move provides a unique contribution to, and lays the groundwork for, future prenatal physical activity intervention strategies, not only in the Eastern Cape Province but throughout South Africa as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-stage approach was utilized, with Phase I focussing on the empirical findings on facilitators of or barriers to prenatal physical participation in Buffalo City Municipality, Eastern Cape Province, which then lays the groundwork for the development of a prenatal physical activity strategy [24][25][26][27]. Therefore, the results of the studies above have provided us with guidance into developing an effective prenatal physical activity strategy that promotes the practice of prenatal physical activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that despite the rise of social media and Internet usage, mass media was declining as a primary source of health information which could have been influenced by low literacy and income among the women. Okafor and Goon 16 found that a majority of women in South Africa (70.2%) got information about physical exercise during pregnancy through social media, television, and radio, while 49.1% used books, newspapers, and magazines as a source of information. The study showed that lack of physical activity information from midwives in charge of their antenatal care clinic influenced high reliance on friends, family, magazines, and most importantly the Internet as a source of information.…”
Section: Related Workmentioning
confidence: 99%
“…It is well known that exercise during pregnancy has a positive effect on the health of both the pregnant woman and the fetus [ 1 , 2 ]. Maternal benefits include reduced risk of excessive gestational weight gain, gestational diabetes mellitus, preeclampsia and hypertension, operative deliveries, postpartum and perinatal depression, and anxiety [ 7 , 8 , 9 ]. Additionally, PA improves maternal cardiorespiratory capacity and fitness level [ 9 ].…”
Section: Introductionmentioning
confidence: 99%